2000
DOI: 10.2460/ajvr.2000.61.446
|View full text |Cite
|
Sign up to set email alerts
|

Use of specific sugars to inhibit bacterial adherence to equine endometrium in vitro

Abstract: Mannose and N-acetyl-D-galactosamine appear to play a role in adhesion of S. zooepidemicus, P. aeruginosa, and E. coli to equine endometrium. In horses with uterine infections, use of sugars to competitively displace bacteria from attachment sites on cells may provide an adjunct to antibiotic treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…We reviewed the published literature and found that there was strong evidence for a positive link between adherence, the presence of fimbriae, and mannosebinding activity by bacteria (Harper et al, 1978;Ofek and Beachey, 1978;Sharon, 1987Sharon, , 2006. For several (Stepinska and Trafny, 1995;King et al, 2000;McEwan et al, 2008). Earlier studies have shown that at least three different types of lectin-like proteins are responsible for the attachment of the saccharide structures of epithelial cells to the adherence proteins of gram-negative bacteria, which are mediated in a mannose-sensitive manner.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the published literature and found that there was strong evidence for a positive link between adherence, the presence of fimbriae, and mannosebinding activity by bacteria (Harper et al, 1978;Ofek and Beachey, 1978;Sharon, 1987Sharon, , 2006. For several (Stepinska and Trafny, 1995;King et al, 2000;McEwan et al, 2008). Earlier studies have shown that at least three different types of lectin-like proteins are responsible for the attachment of the saccharide structures of epithelial cells to the adherence proteins of gram-negative bacteria, which are mediated in a mannose-sensitive manner.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all isolates of E. coli , as well as other members of the Enterobactericeae, such as Enterobacter, Klebsiella, Shigella , and Salmonella , attach to mannose receptors by means of type 1 fimbriae 2–6. Other bacteria also possess mannose‐specific adhesins, but other than type 1 fimbriae, these include Pseudomonas, Vibrio cholerae, Lactobacillus, Streptococcus zooepidemicus , the plant pathogen Ralstonia solanacearum , and the cyanobacterium Microcystis aeruginosa 7–12…”
Section: Introductionmentioning
confidence: 99%
“…The glycoprotein secretions of uterine glands and the carbohydrates of the glycocalyx are important markers for differentiation and functionality. Glycoconjugates are known to promote bacterial attachment to the endometrial cell surface (King et al 2000), which is of importance in the emergence of pyometra, if the invasion of the uterus with Escherichia coli is leading to metritis (Johnston et al 2001). Therefore, any alterations of the glycocalyx on the epithelial surface are noteworthy.…”
Section: Discussionmentioning
confidence: 99%